Influence Analysis and Load Reduction Design of Embankment Filling on Overlying Water Conveyance Tunnel - LYU Li; SUN Bo; TAN Cai (Renmin Zhujiang)
Embankment filling will have adverse effects on the structure of the overlying water conveyance tunnel.In order to reduce the impact of embankment filling on the overlying water conveyance tunnel,a load reduction plan was proposed by setting cast-in-place piles on both sides of the tunnel.Finite element analysis was used to simulate the water conveyance tunnel without load reduction of cast-in-place piles and that with load reduction and reinforcement of cast-in-place piles under different pile spacing,pile elastic modulus,and pile row numbers.At typical section facility monitoring points,the top arch and arch waist of the tunnel lining were monitored.The stress and deformation of the connection points between the side wall,bottom plate,and side wall and bottom plate were analyzed,and the sensitivity of pile spacing,pile elastic modulus,and pile row number to the tunnel load reduction effect was analyzed.The results indicate that:① Embankment filling will cause a vertical deformation of 5.45 cm in the top arch of the tunnel lining,and the tensile stress on the concrete at the junction of the side wall and floor will reach 8.34 MPa,exceeding the allowable value of the structural tensile strength.The lining is in an unsafe state.② By setting cast-in-place piles,the adverse effects of embankment filling on the water conveyance tunnel can be effectively reduced,and the safety of the water conveyance tunnel can be improved.③ The load reduction effect of the water conveyance tunnel is significantly correlated with the pile spacing and pile row numbers,while the correlation with the elastic modulus is relatively small.